2014
DOI: 10.1007/s00240-014-0677-9
|View full text |Cite
|
Sign up to set email alerts
|

Minipercutaneous nephrolithotomy in infants: a single-center experience in an endemic region in Turkey

Abstract: The objective of the study is to evaluate the effectiveness and safety of miniaturized percutaneous nephrolithotomy (mini-PNL) method in infantile patients <3 years of age diagnosed with renal stones. We studied 48 renal units in 40 patients of infantile patients <3 years of age who underwent mini-PCNL at our institute. The mean age of the patients was 24.02 (5-36) months. The mean diameter of the stones was 22.3 mm (11-45 mm). Intrarenal access was achieved under fluoroscopic (n = 43) or ultrasonographic (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
5
11
2
Order By: Relevance
“…As it was in our study, Bodakci et al used only pneumatic lithotoripsy for fragmentation and SFR was 81.2% in their series (20). Brodie and Bo Xiao et al used both pneumatic and laser lithotripsy for fragmentation depending on the surgeon's preference and SFR was 76% and 92.5% in their studies,respectively (21,22).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…As it was in our study, Bodakci et al used only pneumatic lithotoripsy for fragmentation and SFR was 81.2% in their series (20). Brodie and Bo Xiao et al used both pneumatic and laser lithotripsy for fragmentation depending on the surgeon's preference and SFR was 76% and 92.5% in their studies,respectively (21,22).…”
Section: Discussionsupporting
confidence: 58%
“…Pediatric patients were more likely to bleed during system dilatation because of the fragile renal parenchyma and delicate collecting system. In mini PNL series of infancy, blood transfusion rates were lower than the pediatric age patients and varied between 0% and 7.5% (20,21). Studies showed that blood transfusion rates were higher with the use of 24-26Fr sheaths than with ≤18Fr (5.9%) sheaths (24).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Unlike in adults and in older children, the management of large stones in infants requires a high level of performance and experience; we believe that an SFR of 80 % for PNL monotherapy in infants (<1 years) is acceptable. Generally, higher SFRs (73-96 %) have been reported in PNL series in the pediatric age group [6,16,17]. Bodakçi et al reported SFRs of 81.2 % in infantile patients less than 3 years of age using mini-PNL monotherapy [17].…”
Section: Discussionmentioning
confidence: 96%
“…If PNL procedure is performed with an access sheath of 12F-20F diameter; this procedure is called miniaturized percutaneous nephrolithotomy (mPNL). [4,5] Although described as a minimally invasive technique, PNL has some serious potential complications such as fever, septicemia, adjacent organ injury and bleeding. [6,7] In general, bleeding is limited without the further need of any intervention or manipulation but in some cases blood transfusion, super-selective renal angiography and embolization, open exploration or nephrectomy might be required.…”
Section: Introductionmentioning
confidence: 99%